Implementasi Model Game Based Learning Berbantuan Media Panen Ubur-Ubur dalam Pembelajaran Akidah Akhlak di Kelas IX MTsS Al-Manar - Rara Maulani; Zulfani Sesmiarni (Lembaga Yasin AlSys, 2026)
Although the implementation of the Game-Based Learning model in Islamic Religious Education has been widely studied, research specifically examining its application with the support of non-digital game media in Akidah Akhlak instruction at madrasahs remains limited. This study aimed to describe the implementation of the Game-Based Learning model supported by the Panen Ubur-Ubur media in Akidah Akhlak instruction and to analyze the responses and active participation of ninth-grade students at MTsS Al-Manar during the learning process. This study employed a qualitative approach with a descriptive design. The participants consisted of an Akidah Akhlak teacher and ninth-grade students selected through purposive sampling. Data were collected through observations, interviews, documentation, and field notes and were subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, which comprises data reduction, data display, and conclusion drawing. The results showed that the Game-Based Learning model supported by the Panen Ubur-Ubur media was implemented systematically through the preliminary, core, and closing stages. The implementation of the model promoted greater enthusiasm, active participation, collaboration, and student involvement during the learning process. However, its implementation still encountered constraints related to limited time and the low self-confidence of some students during the initial stage of learning. These findings reinforce the relevance of constructivism, experiential learning, and student engagement in Akidah Akhlak instruction and offer an innovative learning alternative that teachers can implement. Future research should examine the effectiveness of this model across more diverse contexts, educational levels, and subjects.